1996
DOI: 10.1016/s1048-9843(96)90027-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness correlates of transformational and transactional leadership: A meta-analytic review of the mlq literature

Abstract: Sivasubramaniam, N. (1996)A meta-analysis of the transformational leadership literature using the Multifactor Leadership Questionnaire (MLQ) was conducted to (a) integrate the diverse findings, (b) compute an average effect for different leadership scales, and (c) probe for certain moderators of the leadership style-effectiveness relationship. Transformational leadership scales of the MLQ were found to be reliable and significantly predicted work unit effectiveness across the set of studies examined. Moderator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

104
1,649
14
94

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,021 publications
(1,952 citation statements)
references
References 51 publications
104
1,649
14
94
Order By: Relevance
“…Furthermore, and probably most importantly in the current economy, transformational leaders are able to enhance their followers' in-role and extra-role performance (Lowe, Kroeck, & Sivasubramaniam, 1996).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Furthermore, and probably most importantly in the current economy, transformational leaders are able to enhance their followers' in-role and extra-role performance (Lowe, Kroeck, & Sivasubramaniam, 1996).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Evidently, these researchers were inspired by theories of charismatic and transformational leadership (Bass, 1985;Bass & Avolio, 1993;Conger & Kanungo, 1987House, 1977;Shamir et al, 1993). In general, transformational and charismatic leadership is considered to result in an increased sense of collective identity and common mission, higher leader effectiveness, greater levels of commitment and motivation, the willingness to make personal sacrifices, and, ultimately, heightened performance (Bass & Avolio, 1993;Lowe, Kroeck, & Sivasubramaniam, 1996;Shamir et al, 1993). Although different theories of charismatic and transformational leadership may have their own explanation for why exactly these effects on followers occur and may accentuate different aspects of leader behavior, most of them emphasize behaviors of the leader that show his or her dedication to the group and its mission (cf.…”
Section: Self-sacrifice and Leadership Effectivenessmentioning
confidence: 99%
“…In these instances, the supervisor is actively monitoring the performance of the employee and takes action when an error occurs [22]. Whilst such behavior from managers is sometimes not as effective in inducing performance as transformational leadership behaviors, meta-analyses have shown that it is still significantly related to overall leadership effectiveness [20,23,24]. Moreover, its substantial presence in blue-collar industries [e.g., 25] creates a need to examine these transactional leadership behaviors.…”
Section: Factors Affecting Motivation To Collect High Quality Datamentioning
confidence: 99%